The material basis of energy transitions - Bleicher, Alena; Pehlken, Alexandra, 1971- (Academic Press, 2020)
"Provides a comprehensive overview of key issues related to the nexus between renewable energy and critical raw materials Explores interdisciplinary perspectives from the natural sciences, engineering and social sciences Discusses critical strategies to address the nexus from a practitioner perspective"--